Priority risk mapping for halal meat production using FMEA method in medium-scale chicken slaughterhouse - Rosyidi, Khafizh; Sucipto, Sucipto; Santoso, Imam; Wibisono, Yusuf (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2025)
The halalness of animal food products, especially chicken meat, is a central issue in the food industry in Indonesia, where the majority of the population is Muslim. Chicken meat is considered a high-risk commodity among consumer food products. This study aimed to identify and evaluate Halal Risk Points (HRPs) in producing male chicken meat in a medium-scale chicken slaughterhouse in Pasuruan Regency, Indonesia. The method used Failure Mode and Effects Analysis (FMEA), by assessing three main parameters, namely Severity, Occurrence, and Detection to calculate the Risk Priority Number (RPN) of each potential risk in the halal production chain. The analysis was carried out with reference to the national halal slaughter standard of SNI 99002: 2016. A total of 17 risk factors were identified and analyzed at five main stages of production, from chicken arrival to final packaging. The results showed variations in RPN, ranging from acceptable risk categories to extreme risks. The slaughtering stage was the most critical stage, with three HRPs categorized as high extreme risk, including the slaughterer is not halal certified (RPN = 350), the cutting point is not correct (RPN = 378), and the chicken is not completely dead after slaughter (RPN = 420). These risks were directly related to violations of Sharia principles and require immediate mitigation actions. Other moderate to low risks were found in hot water soaking, offal removal, and product labeling stages. This study confirmed that the FMEA method was effective in systematically identifying halal risks in chicken slaughterhouse operations. The findings provide a strong basis for implementing risk mitigation strategies, such as standardization of procedures, labor certification, and utilization of monitoring technology to strengthen halal assurance and regulatory compliance.